Quantitative pharmacodynamics functional evaluation of Chinese medicine Qizhu formula in mice with dynamic near-infrared photoacoustic imaging - Qing-Juan Wu; Lan-Yu Chen; Quan-Mei Sun; Ning Wang; Dong Han; Wen-Liang Lv (Photoacoustics)
Background & Aims: Effective anti-fibrotic drugs and new non-invasive evaluation methods for liver fibrosis (LF) are urgently needed. Our study aimed to evaluate the histological effects of the Qizhu (QZ) formula on LF and to explore a non-invasive Near-infrared photoacoustic imaging (NIR-PAI) kinetic model for liver function detection and pharmacodynamic evaluation. Methods: C57BL/6 J mice were randomly divided into six groups (n=6). An LF model was induced by CCl4 for 8 weeks, followed by an 8-week treatment period. Histological and serological parameters were assessed, and indocyanine green (ICG) metabolism (maximum peak time [Tmax] and half-life [T1/2]) was monitored by NIR-PAI. Spearman correlation analysis was conducted to evaluate correlations. Results & Conclusions: Histological and serological results confirmed the anti-fibrotic effects of QZ. NIR-PAI kinetic parameters indicated that QZ shortened the Tmax and T1/2 of ICG. There were good correlations between ICG metabolism and liver histopathology. The non-invasive NIR-PAI kinetic model shows potential in liver function detection and pharmacodynamic evaluation.